Towards a safer world of banking : bank regulation after the subprime crisis - Mohan, T. T. Ram, 1956- (Finance and financial management collection., 2017)
In 2007, the United States faced a financial crisis that severely impacted the U.S. economy as well as the world economy. Indeed, the financial crisis of 2007 has been characterized as the worst since the Great Crash of 1929. The world economy is yet to recover from the impact. This book seeks to address a number of issues thrown up by the crisis of 2007: Why do banking crises happen so often and why is their impact so severe? What were the main causes of the subprime crisis? In terms of bank regulation, what steps have been taken to prevent such crises in the future and make banking safer? Is banking today indeed safer than in 2007? If not, what are the issues that remain to be addressed in regulatory terms? The book contends that, while several factors can be blamed for the financial crisis of 2007, a failure of regulation was the most important one. After assessing the changes to bank regulation that have happened since, it concludes that these are not good enough to make the banking system considerably safer than before. It argues that we need to look at radical, out-of-the-box solutions if another major financial upheaval is to be prevented. The book is aimed primarily at students of business management, economics and international economics, and at bank executives. It should also be of interest to general readers who are curious to know what the subprime crisis was all about.